Can we transform global education without transforming how we monitor progress? - Aaron Benavot; James Williams (Emerald Publishing, 2023)
Purpose - This paper critically aims to review existing monitoring strategies of Target 4.7 of the Sustainable Development Goals and proposes an alternative approach for reporting country progress on relevant Target 4.7 themes. Since this target constitutes one of the most ambitious and transformative education targets there is considerable value in developing a comprehensive reporting and monitoring strategy. Design/methodology/approach - The paper draws on key policy documents to clarify processes leading up to the definition and measurement of a global indicator for Target 4.7. It also discusses limitations associated with the current reporting and measurement strategy. Findings - The paper finds that the current monitoring approach to Target 4.7, based on an existing reporting mechanism for the 1974 Recommendation concerning Education for International Understanding, Co-operation and Peace and Education relating to Human Rights and Fundamental Freedom, is unfit for purpose and needs to be overhauled. The current process for revising the 1974 Recommendation is unlikely to result in a new monitoring strategy that would address existing weaknesses in the current strategy. Originality/value - To the best of the authors' knowledge, a critical review of measurement, reporting and monitoring strategies of Target 4.7 has not been undertaken. Also new in this paper is the proposed global observatory of Target 4.7 policies, practices and initiatives, which, if established, would work to: (1) create a more dynamic and informative monitoring infrastructure; (2) foster peer learning among countries; and (3) identify notable strategies of national, regional and international action in relation to Target 4.7.